Enhancing Chinese SME performance through innovative HR practices - Zheng, C.; O'Neill, Grant; Morrison, M. (MCB University Press, 2009)
Purpose – The purpose of this paper is to show how understanding of human resource (HR)management practices which have been adopted in the emerging markets such as that in China isparticularly interesting to academia and management practitioners. The purpose of this study is toshed some light on the implementation of innovative HR practices among 74 Chinese small andmedium-sized enterprises (SMEs) and to explain how the HR practices influence their firmperformance.Design/methodology/approach – Cluster analysis is used to group Chinese SMEs according totheir adoption of innovative human resource (HR) practices and examine how the practices areassociated with HR outcomes and firm performance.Findings – It is found that the membership of clusters is influenced by several factors, includingownership, age and size of firms. These characteristics have influenced the motivation, capacity andability of firms in the sample to adopt high performance human resource practices. The extent towhich firms have adopted innovative human resource practices is shown to be closely associated withhuman resource outcomes and firm performance.Originality/value – The key implication is that SMEs, especially those rapidly developing domesticand collectively owned small firms, as well as those state-owned enterprises in China, may see clearlythe benefits of devoting greater attention to HR practices to achieve their future growth potential.